2020
DOI: 10.5194/bg-17-6475-2020
|View full text |Cite
|
Sign up to set email alerts
|

Silicon uptake and isotope fractionation dynamics by crop species

Abstract: Abstract. That silicon is an important element in global biogeochemical cycles is widely recognised. Recently, its relevance for global crop production has gained increasing attention in light of possible deficits in plant-available Si in soil. Silicon is beneficial for plant growth and is taken up in considerable amounts by crops like rice or wheat. However, plants differ in the way they take up silicic acid from soil solution, with some species rejecting silicic acid while others actively incorporate it. Yet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 75 publications
(128 reference statements)
2
13
0
Order By: Relevance
“…Regardless of Si supply levels, we found 28 Si enrichment in the entirety of the rice plants relative to the external solution. Similar phenomena were also found by Frick et al (2020) in wheat (Triticum aestivum L.), tomato (Solanum lycopersicum L.), and mustard (Sinapis alba L.) cultured in nutrient solution. This isotope fractionation was assumed to be caused by the difference between the diffusion coefficients of 28 Si(OH) 4 and 30 Si(OH) 4 .…”
Section: Discussionsupporting
confidence: 78%
“…Regardless of Si supply levels, we found 28 Si enrichment in the entirety of the rice plants relative to the external solution. Similar phenomena were also found by Frick et al (2020) in wheat (Triticum aestivum L.), tomato (Solanum lycopersicum L.), and mustard (Sinapis alba L.) cultured in nutrient solution. This isotope fractionation was assumed to be caused by the difference between the diffusion coefficients of 28 Si(OH) 4 and 30 Si(OH) 4 .…”
Section: Discussionsupporting
confidence: 78%
“…The vertical envelope between the dotted lines shows the array defined by the expanded uncertainty (U, k = 2) around the arithmetic mean of the full procedure replicates for each reference material. n = 3, Frick et al 2020). These published analyses were performed at GFZ using the same protocol in the same laboratory as reported for GFZ in this study.…”
Section: Individual Results For Plant Reference Materials Erm-cd281mentioning
confidence: 99%
“…In addition to the data acquired during this study, another published result for ERM‐CD281 is available ( δ 30 Si = −0.28 ± 0.08‰, 2 s , n = 3, Frick et al . 2020). These published analyses were performed at GFZ using the same protocol in the same laboratory as reported for GFZ in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Phytogenic silica can be found in living plants within cells (i.e., in the cell wall and the cell lumen), forming relatively stable, recognizable phytoliths, or in intercellular spaces and extracellular (cuticular) layers forming relatively fragile silica structures [108,109]. Phytogenic Si can be found in almost any plant organ, e.g., in leaves and stems as well as in roots [110,111]. Phytoliths can be frequently found in most soils and show a specific morphology that can be used for the taxonomic identification of plants [108,109,112].…”
Section: Plants and Phytogenic Silicamentioning
confidence: 99%
“…Si absorption by plants is controlled by specific influx (called Lsi1 and Lsi6) and efflux (called Lsi2) channels, which have been found especially in crops such as rice (Oryza sativa), wheat (Triticum aestivum), or sorghum (Sorghum bicolor) (see Ma and Yamaji [119] for a detailed review). However, it should be kept in mind that the mechanisms behind the uptake, transport, and accumulation of Si in plants (active vs. passive Si transport) as well as Si-induced plant resistance (mode of action of Si in plants) are still not fully understood, and thus are under controversial discussion (see, e.g., Frick et al [110], Coskun et al [120], Exley et al [121], and Exley [122]). For example, it was found that plant functional groups strongly affect Si stocks in aboveground biomass, with grasses increasing and legumes decreasing the aboveground biomass Si stocks [123].…”
Section: Plants and Phytogenic Silicamentioning
confidence: 99%